1999
DOI: 10.1097/00005537-199910000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Aural Symptoms and Signs of Temporomandibular Disorder in Association With Treatment Need and Visits to a Physician

Abstract: In patients with otalgia, infectious otolaryngologic diseases should be ruled out. Then the patients without infection should be remitted to a dentist with stomatognathic experience. In the absence of temporomandibular disorders, further medical consultations (e.g., otorhinolaryngological, neurological, physiatric, and psychiatric) are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0
11

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 9 publications
4
40
0
11
Order By: Relevance
“…Other symptoms that presented significant frequency in our study were neck pain 3,4 and teeth sensitivity 28,30 . The high incidence of otological symptoms in the present sample was in agreement with the literature 4,5,6,8,9,27,28 , in which ear fullness prevailed over the symptom of otalgia 2,12,30 . Tinnitus was as frequent as ear fullness.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Other symptoms that presented significant frequency in our study were neck pain 3,4 and teeth sensitivity 28,30 . The high incidence of otological symptoms in the present sample was in agreement with the literature 4,5,6,8,9,27,28 , in which ear fullness prevailed over the symptom of otalgia 2,12,30 . Tinnitus was as frequent as ear fullness.…”
Section: Discussionsupporting
confidence: 93%
“…Subjects with more severe/ intense pain in the muscles and TMJ were more prone to otalgia 12 and tinnitus 3 , which normally require active treatment of TMJ 6 . Neck pain was also positively correlated with otological symptoms 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to know that symptoms of the ear are not present in over 50% of the patients who express otic complaints such as retroauricular and/or preauricular pain, tinnitus, vertigo, hearing impairment, otic fullness, and ear popping sensations. (Gelb et al, 1959;Gelb & Tarte, 1975;Kuttila et al, 1999;Kuttila et al, 2001). Bernhardt et al, (2004) found a significant correlation between tinnitus and TMD, affirming that TMD might cause otologic symptoms.…”
Section: Introductionmentioning
confidence: 98%
“…[6][7][8][9][10] In the temporomandibular joint -disordered population tinnitus prevalence is between 12-68%. [11][12][13][14] Although this is a common problem, it has not been studied in detail. The mechanism of tinnitus and factors influencing it have not yet been revealed.…”
mentioning
confidence: 99%